Deceptive Patterns under a Sociotechnical View - Baroni, Luiz Adolpho; Pereira, Roberto (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
Deceptive and manipulative design patterns are strategies to mislead users or serve the particular interests of third parties other than the user. These patterns are widespread across software, web, and applications, with a notable example being the deliberate placement of commitment terms in obscure, hard-to-read text boxes, concealing clauses related to data sharing. Despite their adoption, these practices persistently degrade user experience and often compromise user privacy and well-being, raising ethical concerns. A systematic literature review conducted in this research reveals a scarcity of comprehensive examinations of deceptive patterns, with most studies focusing on specific aspects in isolation. Addressing this gap, this research characterizes deceptive patterns as a sociotechnical phenomenon that encompasses both human and technical dimensions, dissects a deceptive pattern utilizing the Semiotic Framework, and offers a catalog compiling deceptive patterns and providing accessible resources for users to recognize, understand, and protect themselves against these deceptive practices. Bringing both technical and conceptual contributions, results from evaluating the catalog with HCI specialists suggest its potential to promote awareness of deceptive patterns, and results from adopting a sociotechnical lens to analyze a dark pattern reveal its potential to inform deeper analysis and understanding.